PEOPLE ANALYTICS ADOPTION AND ITS ROLE IN STRATEGIC HUMAN RESOURCE DECISION-MAKING - Aslichah Aslichah; Karina Sukardi; Fahmi Kamal; I Kadek Wira Dharma Prayana; Lusia Adinda Dua Nurak (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study aims to examine the adoption of people analytics and its role in strategic human resource (HR) decision-making. Using a qualitative approach through a systematic literature review, this research analyzes scholarly sources published between 2010 and 2024, including peer-reviewed journal articles, books, and institutional reports. The study applies thematic analysis to identify key patterns related to the level of adoption, determinants, contributions, and challenges of people analytics in organizational contexts. The findings indicate that although people analytics has significant potential to enhance strategic decision-making, most organizations remain at the early stages of adoption, primarily relying on descriptive analytics rather than advanced predictive and prescriptive techniques. The adoption of people analytics is influenced by technological, organizational, and human factors, with human capability—particularly data literacy and analytical skills—emerging as the most critical determinant. Furthermore, people analytics contributes to improving decision quality, supporting workforce planning, enhancing employee retention strategies, and aligning HR practices with organizational objectives. However, several challenges hinder its effective implementation, including data fragmentation, lack of system integration, resistance to change, and ethical concerns related to data privacy and bias. These findings suggest that organizations must adopt a holistic approach by strengthening infrastructure, developing analytical competencies, and fostering a data-driven culture to maximize the benefits of people analytics. In conclusion, people analytics serves as a strategic enabler for modern HR management, but its effectiveness depends on the level of adoption maturity and the organization’s ability to address implementation challenges. Future research is recommended to explore empirical validation and sector-specific applications of people analytics.